2023
DOI: 10.7759/cureus.43156
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Dietary Intake, Bioavailability and Health Benefits of Ellagic Acid (EA) with a Primary Focus on Its Anti-Cancer Properties

Abstract: Ellagitannins (ET) and ellagic acid (EA) are polyphenols, present in common foods, which may exhibit significant health benefits against inflammation, infection and cancer. EA is metabolised by the gut flora to produce urolithins, which are absorbed into the systemic circulation. Urolithins are widely documented to reduce oxidative stress associated with many diseases including cancer, heart disease and liver damage. In particular, Urolithin C and D have been shown to have high anti-oxidant properties through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Indeed, the health benefits attributed to EA-rich foods are thought to involve various protective mechanisms at the cellular level. Dietary EA is converted by the intestinal microbiota to urolithins, which are better absorbed than EA and may contribute significantly to the health effects attributed to EA-rich foods [27]. Among the mechanisms involved in EA pharmacological activities are its ability to reduce the lipidemic profile and lipid metabolism, alter pro-inflammatory mediators (tumour necrosis factor-α, interleukin-1β, interleukin-6), and decrease the activity of nuclear factor-κB while increasing nuclear factor erythroid 2-related factor 2 expression [28].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the health benefits attributed to EA-rich foods are thought to involve various protective mechanisms at the cellular level. Dietary EA is converted by the intestinal microbiota to urolithins, which are better absorbed than EA and may contribute significantly to the health effects attributed to EA-rich foods [27]. Among the mechanisms involved in EA pharmacological activities are its ability to reduce the lipidemic profile and lipid metabolism, alter pro-inflammatory mediators (tumour necrosis factor-α, interleukin-1β, interleukin-6), and decrease the activity of nuclear factor-κB while increasing nuclear factor erythroid 2-related factor 2 expression [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, numerous studies confirmed protective actions exerted by ETs on several pathologies including various forms of cancer and toxic compounds. However, further studies are certainly necessary to better understand the potential applications and the toxicological and pharmacological profile of these substances [20][21][22].…”
mentioning
confidence: 99%